Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1001/jamaneurol.2014.4778
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Cerebral Blood Flow Following Sports-Related Concussion

Abstract: IMPORTANCE Animal models suggest that reduced cerebral blood flow (CBF) is one of the most enduring physiological deficits following concussion. Despite this, longitudinal studies documenting serial changes in regional CBF following human concussion have yet to be performed. OBJECTIVE To longitudinally assess the recovery of CBF in a carefully selected sample of collegiate athletes and compare time course of CBF recovery with that of cognitive and behavioral symptoms. DESIGN, SETTING, AND PARTICIPANTS A cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
196
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(214 citation statements)
references
References 51 publications
(3 reference statements)
11
196
1
Order By: Relevance
“…Concussion affects the autonomic nervous system (ANS) 27,28 and the control of both cerebral blood flow (CBF) [29][30][31][32] and cardiac rhythm. 33,34 The primary ANS control center may be damaged in concussion, particularly if a rotational force was applied to the upper cervical spine, 35 as supported by results from a diffusion tensor imaging study 36 that showed changes to brainstem white matter neurons after concussion.…”
Section: The Physiology Of Concussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concussion affects the autonomic nervous system (ANS) 27,28 and the control of both cerebral blood flow (CBF) [29][30][31][32] and cardiac rhythm. 33,34 The primary ANS control center may be damaged in concussion, particularly if a rotational force was applied to the upper cervical spine, 35 as supported by results from a diffusion tensor imaging study 36 that showed changes to brainstem white matter neurons after concussion.…”
Section: The Physiology Of Concussionmentioning
confidence: 99%
“…24,37 For example, reduced resting CBF has been evident for up to a month postconcussion in some adolescents 31 and collegiate football players. 32 The resolution of this vulnerable period of brain metabolic imbalance after concussion does not necessarily coincide with the resolution of symptoms. Using proton magnetic resonance spectroscopy, Vagnozzi et al 38 showed that metabolic dysfunction can last up to 30 days after SRC and up to 45 days if a second injury occurs before the first has resolved.…”
Section: The Physiology Of Concussionmentioning
confidence: 99%
“…These results suggest that determination of regional CBF detection via neuroimaging has potential as an objective biomarker for tracking symptoms and recovery after concussion. A study of 44 collegiate football athletes showed decreased CBF in the dorsal midinsular cortex (dmIC) and superior temporal sulcus, both of which are important for higher cognitive functioning, as compared with healthy controls one week after injury (43). Furthermore, CBF in dmIC at one-month after injury inversely correlated with concussion severity and symptom resolution (43).…”
Section: Biomarkers Of Cbf Disturbancementioning
confidence: 99%
“…A study of 44 collegiate football athletes showed decreased CBF in the dorsal midinsular cortex (dmIC) and superior temporal sulcus, both of which are important for higher cognitive functioning, as compared with healthy controls one week after injury (43). Furthermore, CBF in dmIC at one-month after injury inversely correlated with concussion severity and symptom resolution (43). Future neuroimaging studies should examine not only functional activity after mTBI but also differences in functional connectivity as potential biomarker candidates (43).…”
Section: Biomarkers Of Cbf Disturbancementioning
confidence: 99%
“…Altered functional connectivity has also been observed relative to executive function, visual, and motor networks [57][58][59][60]. Reduced cerebral blood flow (CBF) has been reported during the acute and sub-acute phases (days to weeks) post-concussion [61][62][63], as well as at more chronic time points (approximately 5 months) [64].…”
Section: Neuroimagingmentioning
confidence: 99%